Machina iuris-dicere potest? (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
With the development of increasingly advanced A.I. systems, it has been suggested on several fronts to make use of predictive algorithms in the jurisdictional system, in the analysis of the cases and formulation of decisions, should they be capable of iuris-dicere like human judges. With a view to ensure the absolute primacy of human decision, the AI-based predictive machine could then support (and not completely replace) the human judge in his/her ruling. In the same way as an Advocate General, the conclusions rendered by the algorithm could thus constitute a mandatory but not binding opinion, which the human judge remains free to disregard, by giving his/her reasoned decision.
Keywords: Artificial Intelligence; predictive algorithm; justice system; robotic sentencing; predic-tive justice